The Big Reset War on Gold and the Financial Endgame - Middelkoop, Willem (Amsterdam University Press, 2016)
Amid the turmoil in the Eurozone, economic problems in Russia, stagnation in Japan, and rumblings that China may slip into recession, the one reliable asset is the American dollar. While it may encounter ups and downs, investors for decades have been confident that it will never lose a substantial part of its value. That may be about to change. In The Big Reset, Willem Middelkoop lays out the case for an inevitable monetary reset, one that will be designed to keep the United States in the driver's seat, but will include strong roles for the Euro and China's Renminbi-and, crucially, gold. This fully revised edition of Middelkoop's book takes into account developments since its original publication, which have only strengthened the case for the coming return of gold.